2020
DOI: 10.3390/cancers12082319
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein (CRP) Levels in Immune Checkpoint Inhibitor Response and Progression in Advanced Non-Small Cell Lung Cancer: A Bi-Center Study

Abstract: Background: Biomarkers for predicting response to immune checkpoint inhibitors (ICI) are scarce and often lack external validation. This study provides a comprehensive investigation of pretreatment C-reactive protein (CRP) levels as well as its longitudinal trajectories as a marker of treatment response and disease outcome in patients with advanced non-small cell lung cancer (NSCLC) undergoing immunotherapy with anti PD-1 or anti PD-L1 agents. Methods: We performed a retrospective bi-center study to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 47 publications
4
65
1
1
Order By: Relevance
“…We recently could show that a doubling of baseline CRP level was associated with a 1.4-fold higher relative risk of disease progression or death and that a 10 mg/mL/ month faster increase in CRP levels over time predicted for 13-fold higher risk of experiencing a PFS event. In addition, a decreasing CRP during the first 8 weeks after ICI initiation was strongly associated with favorable PFS experience (10% reduction in CRP predicted for a 0.9fold reduction in PFS) [118].…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
“…We recently could show that a doubling of baseline CRP level was associated with a 1.4-fold higher relative risk of disease progression or death and that a 10 mg/mL/ month faster increase in CRP levels over time predicted for 13-fold higher risk of experiencing a PFS event. In addition, a decreasing CRP during the first 8 weeks after ICI initiation was strongly associated with favorable PFS experience (10% reduction in CRP predicted for a 0.9fold reduction in PFS) [118].…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
“…Canakinumab being used as a single agent in the CANTOS trial has led to a reduction in CRP from baseline [43]. Several studies reported improved survival in patients with advanced NSCLC treated with anti-PD-L1 inhibitors who experienced a reduction in CRP level [49].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that a systemic and locoregional inflammatory response is induced in the host from the earliest stages of cancer development, assessing the potential of IL-1β blockade in the neoadjuvant setting when the tumor mass and locoregional lymph nodes are intact is a possibility [48]. In a recent, retrospective bi-center study to assess the association between baseline CRP levels and anti-PD-1/PD-L1 treatment in patients with advanced NSCLC (discovery cohort, n = 90; validation cohort, n = 101), pretreatment CRP level was confirmed to predict progressionfree survival and OS [49]. Results of a retrospective analysis of 87 patients with advanced NSCLC receiving anti-PD-1 treatment demonstrated a significant association of baseline CRP with OS after immunotherapy [50].…”
mentioning
confidence: 99%
“…A high neutrophil/lymphocyte ratio (NLR) correlated with an impaired outcome in NSCLC treated with ICI ( 26 ). In addition, serum CRP levels, a routine marker of inflammation, have been suggested to reflect treatment benefit during anti PD-(L)1 treatment in advanced NSCLC ( 27 ).…”
Section: Discussionmentioning
confidence: 99%